Effect of using celery seed as a probiotic on the productive traits of kids local goats - Meitham K. Ali Al-Galiby; Noora. K. J. Ai-Ghazi (University of Thi-Qar Journal of agricultural research, 2022)
The study was conducted in the animal field of the College of Agriculture and Marshes / University of Thi- Qar from 12/30/2021 to 3/15/2022 in order to find out the effect of giving celery base and probiotic to the kids of local goats and its reflection on the productive traits. This origin in the study gave 16 formulas weighing 14.5 kg, and performed randomly on a treatment with four replications for one treatment, T1 treatments: Treating the basic ration consisting of (59% barley, 37% bran, 1% urea, 2% salts, 1% vitamins) and without added, T2 (control treatment + addition of probiotic 2%), T3 (treatment of control + addition of celery seed 5%), T4 (treatment + addition of probiotic with celery). The results of the current study showed that the addition of celery seeds and the probiotic/head/day increased the rate of weight and weight gain. The results of the first week of the experiment showed that there was no significant difference in weight despite the presence of an arithmetic increase in favor of the probiotic and celery treatment, with an average of (15.89) kg compared to With the rest of the treatments, in the second week, the moral superiority was in favor of the two treatments (the probiotic + celery and celery) whose average was 16.37 and 16.54 kg, respectively, and through the results we find a significant superiority in the treatment (the probiotic + celery) for the fourth, sixth and eighth weeks And the tenth and twelfth of the experiment, and the averages recorded for their body weights were (17.300), 18.40, 19.30, 20.30, and 21.30 kg, respectively, compared to the rest of the experiment’s treatments. As for the total weight gain, the moral superiority was in favor of the probiotic treatment, as it recorded an average of (7.15) kg compared to the rest of the treatments (the probiotic + celery, celery, and the control), where the average total weight increases were 5.41, 5.16, 4.19) kg, respectively. Significant superiority was noted in the daily weight gain rate in favor of the probiotic treatment, as it recorded an average daily weight gain of 85.11 (gm/day) compared to the rest of the experiment treatments (the probiotic + celery, celery, control) and the average daily weight gain values ​​were (64.40, 61.42, 49.88)gm/boom, respectively. As for the efficiency of food conversion, it was a significant superiority in favor of the control treatment, as it recorded an average of (10.23) kg of feed / kg compared to the rest of the treatments (the probiotic + celery, celery, the probiotic) and their recorded averages were (8.65, 7.05) , 6.12) kg of feed / kg of weight gain, respectively.